2006
DOI: 10.1080/13504850500404258
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of European spot market prices for natural gas? A real-time analysis of market integration using the Kalman Filter

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…Recent work on global gas markets by Neumann et al (2006), Neumann and Cullmann (2012), and Li et al (2014) has shied away from a cointegration framework where prices are tightly linked in favor of the Kalman filter that captures gradual price convergence. These papers also acknowledge the important role of oil-indexed long-term contracts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work on global gas markets by Neumann et al (2006), Neumann and Cullmann (2012), and Li et al (2014) has shied away from a cointegration framework where prices are tightly linked in favor of the Kalman filter that captures gradual price convergence. These papers also acknowledge the important role of oil-indexed long-term contracts.…”
Section: Resultsmentioning
confidence: 99%
“…Neither paper considers structural change or distinguishes between pairs of trading partners. In Neumann et al (2006) and Neumann and Cullmann (2012), the authors relax the assumption of a stable empirical pricing relationship, but remain within the framework of a spot-market. Using a timevarying Kalman filter, they show that European gas markets have become more tightly integrated over time.…”
Section: Empirics: Cointegration and Lng Pricesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the UK market, that has been liberalized 15 years earlier than Continental Europe, Panagiotidis and Rutledge (2007) show that the linkage between the natural gas price and the price of oil has become more volatile over time which can be interpreted as a sign of decoupling of the natural gas price from the oil price. Neumann et al (2006) have shown that integration between the UK market and the largest Continental European wholesale market (Zeebrugge) works well, but that price convergence between different Continental European markets is still to come about. Last but not least, Siliverstovs et al (2005) were the first to address the issue of international market integration for natural gas; they concluded that for the period preceeding liberalization of natural gas markets in Europe, i.e.…”
Section: Introductionmentioning
confidence: 99%